Change in Hematological disturbances in Malaria in Eastern India: an observational study (Bangladesh Journal of Medical Science, 2016)
Objectives: We wanted to find out the change and pattern of hematological disturbances in patients suffering from malaria and whether the hematological disturbances had any correlation with morbidity in them.Materials and methods: In a retrospective, observational study, first 100 admitted malaria patients in a tertiary medical institute in Kolkata, was taken from August 2009 to July 2011 and their demographic, clinical and laboratorial records were noted and analysed.Results: Seventy-one patients (71%) had anemia, ninety patients (90%) had thrombocytopenia, twenty-six patients (26%) had leucopenia and two patients (2%) had leukocytosis. Vivax malaria patients had lower platelet count than their falciparum counterparts, whereas falciparum malaria patients had lower hemoglobin, packed cell volume and higher total leukocyte count; all these hematological disturbances were found to be correlated with higher morbidity in patients suffering from malaria.Conclusion: In patients suffering from malaria, there was high incidence of hematological disturbances which was changing pattern and also correlated with morbidity.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.403-408